Description of a model to optimise the feeding of amino acids to growing pullets - Bonato, M. A. [UNESP]; Sakomura, N. K. [UNESP]; Gous, R. M.; Silva, E. P. [UNESP]; Soares, L. [UNESP]; Peruzzi, N. J. [UNESP] (Taylor & Francis, 2016)
Abstract: 1. A nutrition model is described that may be used to optimise the amino acid nutrition of laying-type pullets prior to the onset of lay. It is not a method of optimising lifetime laying performance. 2. The potential growth and composition of the body, feathers, ovary and oviduct are described from hatching to the age at which sexual maturity is attained, from which the daily amino acid and energy requirements for the average individual in the population can be calculated. 3. There are two parts to the approach used, the first being a description of the model itself and the second being a description of how the required information was gathered. A number of assumptions made in developing the model are discussed. 4. The rates of maturing of the body, feather-free body and body protein of the DeKalb pullets used were shown to be constant at 0.017/d and those of feathers at 0.02/d. These are considerably slower than those of the oviduct and ovary (0.139 and 0.084/d respectively). The ovary attained a higher mature weight (78.4 vs. 58.7 g) than the oviduct. 5. The age at which the growth of the reproductive organs is initiated in the model is defined by the user. The daily amount of threonine required to meet the requirements for maintenance and potential growth of the developing tissues and organs is calculated for each day of the growing period from hatching to the age at which the first egg is laid. A method of calculating the required daily concentration of threonine in the feed is described, from which a feeding programme may be derived. 6. For the model to produce an optimum economic feeding programme for a population of laying-type pullets, more information than is available from this study is required. These issues are discussed in the paper.